Carbonous metallic framework of multi-walled carbon Nanotubes/Bi2S3 nanorods as heterostructure composite films for efficient quasi-solid state DSSCs. (1st September 2018) - Memon, Anam Ali; Patil, Supriya A.; Sun, Kyung Chul; Mengal, Naveed; Arbab, Alvira Ayoub; Sahito, Iftikhar Ali; Jeong, Sung Hoon; kim, Hak Sung
Abstract: Bismuth sulfide (Bi2 S3 ); is a non-toxic metal chalcogenide and a promising semiconductor in energy storage devices, but it has not received much attention in the regime of dye sensitized solar cells (DSSCs). The present research describes the synthesis of highly electro-catalytic active counter electrode (CE) material for quasi-solid state dye sensitized solar cells (QDSSCs), namely carbonous metallic heterostructure composite (CMHC), composed of solution processed bismuth sulfide nanorods and modified Multi walled carbon nanotubes (MWCNTs). Due to the positive synergistic effect of conductive MWCNT network and rod-like morphology of bismuth sulfide, the composite exhibits multifunctional characteristics of high conductivity, superior electro-catalytic activity and optimal porosity. The carbonous composite with a dominant oxygen rich surface shows enhanced electro-catalytic activity, low charge transfer resistance (RCT ), and exceptional cyclic stability as compared with pristine bismuth sulfide. The as-synthesized composite exhibit a very low charge transfer resistance of 0.9 Ω which signifies a fast electron transport mechanism. The suggested composite CE with 3% polymer gel electrolyte achieves a high efficiency of 8.24% comparable to Pt (8.47%). Based on the facile synthesis of composites and excellent performance of CE, the designed quasi-solid state dye sensitized solar cells stand out as an efficient next generation solar cells.